THE RELATIONSHIP BETWEEN BLOOD SUGAR LEVELS AND BLOOD PRESSURE IN PATIENTS WITH TYPE II DIABETES MELLITUS IN THE WORKING AREA OF THE HEALTH CENTER : Muhammad Rafka Hagi Suarna, Egi Mulyadi, Amir Hamzah - Muhammad Rafka Hagi Suarna; Egi Mulyadi; Amir Hamzah (PROFESSIONAL HEALTH JOURNAL, 2026)
Diabetes mellitus is a chronic disease that requires prolonged treatment therapy to reduce the incidence of complications. The purpose of this study is to determine the data that can increase a person's risk of developing diabetes mellitus, such as age, weight, family history, lifestyle, and diet and to determine whether high blood sugar levels contribute to an increased risk of blood pressure in type II diabetes mellitus patients. The method used is correlation with a cross sectional approach emphasizing the time of measurement or observation of data on the independent variable and the dependent variable only once, at a time. The population in this study is the number of patients who have a history of type 2 diabetes mellitus in the Ciracap Health Center working area of 94 people. This study will use 55 respondents, using the slovin formula. The sampling technique used in this study was non-probability sampling with a purposive sampling approach. The results showed that the P Value obtained from the Chi Square test for asymp sig. (2-sided) is 0.002. This value shows the result of p <0.05 and means that Ha is accepted and H0 is rejected. So it can be concluded that there is a significant relationship between blood sugar levels and blood pressure in patients with diabetes mellitus II in the Ciracap working area.